The Evaluation of Omnibus Law on Job Creation on Domestic Investment in Java: Evaluation of the Difference-in-Differences Approach - Martua, Aleknaek; Putra, Budya Pryanto; Satria, Imam (Monas: Jurnal Inovasi Aparatur, 2024)
To improve welfare, economic development is a complex and continuous process and investment is one of the important components. The Omnibus Law on Job Creation in 2020 (UUCK 2020) is a legislative policy and came into force in November 2020 with the aim of increasing the ease of doing business and attracting investment, thereby increasing jobs. Through the implementation of the OSS RBA system, UUCK 2020 brings major changes in business licensing governance that prioritizes legal certainty, transparency, and speed in the licensing process. The phenomenon of Java-centric is slowly developing until now has referred to various aspects including spatial, economic, social, cultural, political and other aspects. This study answers the hypothesis about the impact of the UUCK 2020 supported by the RBA OSS can increase domestic investment and also answers the evidence of the continued influence of Centric Java in increasing domestic investment caused by the regulation. This research study uses quantitative methods with difference in difference method against 34 provinces grouped in treatment and control groups. The results obtained are descriptive and empirically proven that there is a more expansive trend for the treatment group (Java island) after the UUCK 2020 policy is applied.This research study confirms the existence of investment preferences that are still focused and concentrated in Java compared to Non-Java.